2014
DOI: 10.2146/ajhp140039
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a phenytoin loading dose program in the emergency department

Abstract: No change in the percentage of optimal phenytoin loading doses in the ED was observed after implementation of a combined pharmacist- and physician- dosing program. When stratified into pharmacist or prescriber dosing, the pharmacist-led dosing program significantly improved the proportion of patients who received optimal phenytoin loading doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…However, in their conclusions the authors also suggest a dose cap of 2000 mg for patients although this was not specifically addressed in their study. In a more recent report looking at the implementation of a phenytoin loading dose program in the ED, the researchers implemented a protocol that adjusted dosing based on the patient's body mass index, but limited all single doses to no more than 2000 mg . In patients presenting with body weights above 100 kg, the use of the recommended dosing strategy of 20 mg/kg will always exceed this proposed maximum.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, in their conclusions the authors also suggest a dose cap of 2000 mg for patients although this was not specifically addressed in their study. In a more recent report looking at the implementation of a phenytoin loading dose program in the ED, the researchers implemented a protocol that adjusted dosing based on the patient's body mass index, but limited all single doses to no more than 2000 mg . In patients presenting with body weights above 100 kg, the use of the recommended dosing strategy of 20 mg/kg will always exceed this proposed maximum.…”
Section: Discussionsupporting
confidence: 90%
“…Similar results have been found by other investigators in other inpatient settings, often as aspects of pharmacokinetic monitoring services . Only one other group of researchers has explored the impact of an EPh as part of a comprehensive phenytoin loading dose program on the dosing of this agent in the ED . They found a significant improvement in the administration of optimal phenytoin doses (15‐18 mg/kg) in the presence of an EPh (82% vs 50%; P = 0.007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that pharmacistled dosing programs significantly improved the proportion of patients who received optimal PHT LDs in comparison to prescriber-led programs (82% vs. 49%), and that a 1000 mg LD was used less frequently in the pharmacist-led group (42.9 vs. 65.1%). 23 A similar trend was found for PHT MDs; however, it was not as clear. Patients who received a standard dose of 400 mg/day or a weight-based dose >5 mg/kg per day showed a trend to be equally likely within therapeutic range.…”
Section: Discussionsupporting
confidence: 52%
“…However, this finding has been previously supported and the authors have recommended avoidance of preset PHT LDs. 22 This trend is further explained in a study by Brancaccio et al, 23 which suggested that a fixed dosing strategy of 1000 mg may be used because of prescriber familiarity; however, with the rates of obesity increasing, this approach may lead to a large proportion of patients failing to achieve therapeutic concentrations, subsequently impacting patient outcomes. Interestingly, Brancaccio et al explored the impact of a PHT LD program, which was further stratified into pharmacist-led and prescriber-led.…”
Section: Discussionmentioning
confidence: 99%